Thermodynamic and Transport Study of Electron- and Hole-Doped MGa3 Single Crystals (M = Fe, Co) - Cabrera-Baez, M.; Magnavita, E. Thizay; Ribeiro, Raquel A.; Avila, Marcos A. (Journal of electronic materials, 2014)
FeGa 3 and related compounds have been subjects of recent investigation for their interesting thermoelectric, electronic, and magnetic behaviors. Here, single crystals of FeGa 3− y Ge y were grown by the self-flux technique with effective y = 0, 0.09(1), 0.11(1), and 0.17(1) in order to investigate the evolution of the diamagnetic semiconducting compound FeGa 3 into a ferromagnetic metal, which occurs through the electron doping and band structure modifications that result from substitution of Ge for Ga. Heat capacity and magnetization measurements reveal non-Fermi liquid behavior in the vicinity of the transition from a paramagnetic to ferromagnetic ground state, suggesting the presence of a ferromagnetic quantum critical point (FMQCP). We also present the first results of hole doping in this system by the growth of FeGa 3− y Zn y single crystals, and electron- and hole doping of the related compound CoGa 3 by CoGa 3− y Ge y and CoGa 3− y Zn y crystal growths, aiming to search for further routes to band structure and charge carrier tuning, thermoelectric optimization, and quantum criticality in this family of compounds. The ability to tune the charge carrier type warrants further investigation of the MGa 3 system’s thermoelectric properties above room temperature.